Produção de texto na base nacional comum curricular: análise crítica a partir da teoria histórico-cultural - Ferreira, Priscila Zorzan (2021)
The research addresses the text production in the National Curricular Common Base (BNCC), for literacy classes, performing a critical analysis based on Vygotsky's Cultural-Historical Theory. It seeks to answer the following questions: does BNCC contemplate the production of written text? How can BNCC's text production objectives be analyzed in the light of the Cultural-Historical Theory? The general objective is to critically analyze how the BNCC proposes the production of text for the first, second and third grade of Primary School. The specific objectives are: research the teaching of text production, according to the Cultural-Historical Theory; and analyze the proposals for text production, from the first to the third grade of Primary School, present at BNCC, making a critical analysis from the Cultural-Historical Theory. This is a bibliographic and documentary research, systematized by the analysis of the document of the BNCC for literacy classes. It concludes that the BNCC has objectives aimed mainly at the mechanical teaching of writing, with a focus on structural and grammatical work.